Sequence and Structure Characteristics of 22 Deletion Breakpoints in Intron 44 of the DMD Gene Based on Long-Read Sequencing - Geng, Chang; Tong, Yuanren; Zhang, Siwen; Ling, Chao; Wu, Xin; Wang, Depeng; Dai, Yi (Frontiers in Genetics, 2021)
Purpose Exon deletions take up to 80% of mutations in DMD gene, which will cause Duchenne and Becker muscular dystrophy. Exon 45-55 regions were reported as deletion hotspots and intron 44 harbored more than 25% deletion start points. We aimed to investigate fine structures of breakpoints in intron 44 to find potential mechanisms of large deletions in intron 44. Methods 22 dystrophinopathy patients whose deletion started in intron 44 were sequenced using long-read sequencing of DMD gene capture panel. Sequence homology, palindromic sequences, polypyrimidine sequences were searched at the breakpoint junctions. Repeatmasker was applied to analyze repetitive elements and Mfold was applied to predict secondary DNA structure. Results With a designed DMD capture panel, 22 samples achieved 2.25 gigabases and 1.28 million reads on average. Average depth was 308× and 99.98% bases were covered at least 1×. The deletion breakpoints in intron 44 were scattered and no breakpoints clustered in any region less than 500bp. A total of 72.7% breakpoints located in distal 100kb of intron 44 and more repetitive elements were found in this region. Microhomologies of 0-1bp were found in 36.4% (8/22) patients, which accorded with nonhomologous end-joining. Microhomologies of 2-20 bp were fouond in 59.1% (13/22) patients, which accorded with microhomology-mediated end-joining. Moreover, a 7bp insertion was found in one patient, which might be an evidence of aberrant replication origin firing. Palindromic sequences, polypyrimidine sequences and small hairpin loops were found near several breakpoint junctions. No evidence of large hairpin loop formation in deletion root sequences was observed. Conclusions This study was the first to explore possible mechanisms underlying exon deletions starting from intron 44 of DMD gene based on long-read sequencing. Diverse mechanisms might be associated with deletions in DMD gene.